Room for Improvement : Hydroclimatic Challenges to Poverty-Reducing Development of the Brahmaputra River Basin - Ray, Patrick A.; Yang, Yi-Chen E.; Wi, Sungwook; Khalil, Abedalrazq; Chatikavanij, Vansa; Brown, Casey (Elsevier, 2016)
The Brahmaputra river is the largest (by annual discharge) of the three in the Ganges-Brahmaputra-Meghna (GBM) system, and by itself carries more flow than all but 4 rivers in the world. It is the primary water source for over 130 million people, many of whom are mired in chronic poverty. The potential in the Brahmaputra River basin for poverty-reducing development of agriculture and hydropower is great. However, progress in these sectors and others has been hindered by significant natural and anthropogenic challenges. As they attempt to develop their water resources in a manner that reduces water-related vulnerabilities, the people of the Tibet Autonomous Region of China, Bhutan, Northeast India, and Bangladesh face a number of challenges, including: endemic poverty; floods; droughts; groundwater over-abstraction; political unrest; and the broader development ambitions of the member nations (leading to net import or export of resources from the basin). To those challenges have recently been added climate change and difficult decisions regarding hydropower development. A critical compounding factor in the Brahmaputra basin is the lack of an authoritative, reliable, and comprehensive network of basin-wide information on climate, streamflow, natural hazards, and economic factors, such as agricultural production, prices, and trade. Anthropocentric development in the Brahmaputra basin must balance the goal of immediate poverty reduction with the preservation of the vulnerable, rich natural heritage of the basin, in the interest both of intergenerational human equity, and biocentric egalitarianism. In the space allotted here, we provide a snapshot of the demographic and hydroclimatic characteristics of the basin of greatest concern to water system planners aiming at poverty reduction through sustainable development. We propose that the basin's hydro-climatological, economic, and political complexities are such that a basin-wide water system knowledge platform is needed to organize quantitative thinking on potential water-related investments in the basin.